The intouchables [videorecording (DVD)] - Toledano, Éric; Nakache, Olivier; Cluzet, François; Sy, Omar, 1978-; Le Ny, Anne (Sony Pictures Home Entertainment, 2013)
An irreverent, uplifting comedy about friendship, trust, and human possibility. Based on a true story of friendship between a handicapped millionaire and his street-smart ex-con caretaker, The Intouchables depicts an unlikely camaraderie rooted in honesty and humor between two individuals who, on the surface, would seem to have nothing in common.